2022
DOI: 10.1038/s41598-022-12374-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischemic conditioning on head and neck free flap oxygenation: a randomized controlled trial

Abstract: Flap failure after microvascular reconstructive surgery is a rare but devastating complication caused by reperfusion injury and tissue hypoperfusion. Remote ischemic conditioning (RIC) provides protection against ischemia/reperfusion injury and reduces tissue infarction. We hypothesized that RIC would enhance flap oxygenation and exert organ-protective effects during head and neck free flap reconstructive surgery. Adult patients undergoing free flap transfer surgery for head and neck cancer were randomized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Min, SH et al (2022) 9 showed Remote ischemic conditioning (RIC) did not improve flap tissue oxygenation after head and neck cancer reconstructive surgery. There was evidence of a myocardial-protective role of RIC in the ex vivo I/R injury model using plasma dialysate from patients.…”
Section: Resultsmentioning
confidence: 99%
“…Min, SH et al (2022) 9 showed Remote ischemic conditioning (RIC) did not improve flap tissue oxygenation after head and neck cancer reconstructive surgery. There was evidence of a myocardial-protective role of RIC in the ex vivo I/R injury model using plasma dialysate from patients.…”
Section: Resultsmentioning
confidence: 99%
“… 4 - 6 Although flap perfusion is critical for flap viability and survival and is used as a parameter for flap monitoring, it remains unknown whether the number of ischemia intervals and the duration of ischemia influence microvascular free flap perfusion. 13 - 15 , 19 - 21 Such information may improve the understanding of microvascular free flap perfusion in general, provide potential guidance for controlling the number of ischemia intervals and the ischemia duration, and support the accurate interpretation of flap perfusion measurements in the context of flap monitoring.…”
Section: Discussionmentioning
confidence: 96%
“…Ini pada evaluasi tindakan pasien rawat jalan berusia sembilan belas tahun berusia dua puluh tahun mengalami perubahan hemodinamik dan kesadaran, pasien berusia enam puluh tahun meninggal [20]. RIC akan meningkatkan oksigenasi flap dan memberikan efek pelindung organ selama operasi rekonstruksi flap bebas kepala dan leher [21].…”
Section: Pembahasanunclassified